Keterkaitan Perkembangan Permukiman dan Perubahan Harga Lahan di Kawasan Tembalang - Dodi Pidora; Bitta Pigawati (Jurnal Wilayah dan Lingkungan, 2014)
Tembalang area is planned as location for education, especially for high level education. This function becomes a pull factor for the population to occupy the land which leads to the increase of needs for supporting space. The increase of space requirement for the development of settlement, trade, and service area bring an impact to the land price rising in Tembalang. This research aims to find out the correlation between the settlement development with the land price evolution. The method used is quantitative with the support of spatial analysis. The correlation of settlement development and land price evolution is observed with the score of 0,45 as Pearson Correlation. The correlation is represented mostly in lower land price which directly give effect to the price rising. The largest land expansion for settlement is in radius 1-2 Km which reaches 204% in 2012. Whilst, the land price itself experiences very high increase, especially in the area situated close with UNDIP such as Bulusan Village where the price rising hits 800% from 2002 to 2012.